Karakteristik Peneluran Penyu di Kampung Makimi Nabire Papua Tengah - Irianty Tampubolon; Frits Aripatra Maitindom; Margret Inggrit Solissa (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
The aim of this study was to analyze the characteristics of turtle nests, environmental conditions, and turtle nesting activities. The methods used were field observation techniques and descriptive qualitative data analysis. During the 2025 nesting season (February–August), 11 nests were identified, located approximately 30 m from residential areas. These nests contained a total of 1,442 eggs, with a hatching success rate of 94%, resulting in 1,362 chicks, 53 eggs did not hatch, and 27 chicks died. Analysis of environmental factors showed that nest temperatures ranged from 27 to 31 °C, pH ranged from 5.5 to 7, and humidity levels fluctuated between 50 and 74%. The width of the beach in the intertidal zone is 50 m, with elevations ranging from 6.23 to 11.72%, while the supratidal zone presented elevations from 0.82 to 6.04%. The composition of the sediments varies in weight from 10.08 to 641 g, with fine sand being the dominant particle size (60.05%). The coastal vegetation is dominated by 6 plant species.